2005
DOI: 10.1080/14622200500266114
|View full text |Cite
|
Sign up to set email alerts
|

“Withdrawal symptoms” in adolescents: A comparison of former smokers and never‐smokers

Abstract: Since the early 1980s, investigators have been reporting that adolescent smokers felt "dependent" on cigarettes and that adolescents trying to quit smoking experienced the same withdrawal symptoms observed in adult quitters, including restlessness, insomnia, increased appetite and weight gain, irritability or anger, depression, craving for cigarettes, and trouble concentrating. We hypothesized that most of these symptoms might be attributed to adolescence itself. To investigate this hypothesis, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…It is plausible that second-hand smoke exposure (SHS) explains this unexpected and intriguing observation. Prokhorov et al (2005) found that the prevalence of 5 of 7 withdrawal symptoms was similar in never-and former smokers. Bélanger et al (2008) reported 4.6% of never-smoking 5th graders endorsed at least one ND symptom, and SHS exposure in cars (Hedges g = .09), sibling smoking (g = .14), and peer smoking (g = .…”
Section: Nd Symptoms During Adolescence In Tobacco-naïve Populationsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is plausible that second-hand smoke exposure (SHS) explains this unexpected and intriguing observation. Prokhorov et al (2005) found that the prevalence of 5 of 7 withdrawal symptoms was similar in never-and former smokers. Bélanger et al (2008) reported 4.6% of never-smoking 5th graders endorsed at least one ND symptom, and SHS exposure in cars (Hedges g = .09), sibling smoking (g = .14), and peer smoking (g = .…”
Section: Nd Symptoms During Adolescence In Tobacco-naïve Populationsmentioning
confidence: 90%
“…The unexpected phenomenon of ND symptoms among never-smokers has been repeatedly observed (cf., Bélanger et al, 2008;DiFranza et al, 2000;Okoli et al, 2009;Prokhorov et al, 2005;Racicot et al, 2011a,b). This longitudinal study replicated previous cross-sectional findings, as peer smoking and alcohol use predicted ND symptoms among never-smoking adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents experience symptoms of nicotine dependence (Centers for Disease Control, 1994;Colby et al, 2000;DiFranza et al, 2000DiFranza et al, ,2002Fergusson et al, 1996;Kandel et al, 2005;Karp et al, 2006;McNeill et al, 1986;Nelson and Wittchen, 1998;O'Loughlin et al, 2002O'Loughlin et al, ,2003O'Loughlin et al, ,2004Prokhorov et al, 1998Prokhorov et al, ,2001Prokhorov et al, ,2005Rojas et al, 1998;Sledjeski et al, 2007;Stanton, 1995), although crude rates of dependence are lower among adolescents than adults (Andreski and Breslau, 1993;Anthony et al, 1994;Heishman et al, 1997;Kandel, 2003;Kandel et al, 1997;Kandel and Chen, 2000). Age-specific comparisons based on cross-sectional samples document that rates increase rapidly throughout adolescence up to age 18 when they stabilize (Kandel, 2003;Nelson and Wittchen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents trying to quit smoking frequently report urges to smoke, irritability, and difficulty concentrating [8]. However, it is unclear whether these reported symptoms are distinct from the daily lability experienced by adolescents in general; indeed in one retrospective report on adolescent smokers, reports of withdrawal symptoms (in the last 30 days for nonsmokers and at the time of most recent quit effort for smokers), did not distinguish light smokers from non-smokers [9]. …”
mentioning
confidence: 98%
“…Moreover, the consistent and moderately severe cravings may result in behaviors with serious consequences for the adolescent, such as smoking in school or missing class to smoke. Additional research is required to assess the relative contributions of nicotine withdrawal and cravings to daily school performance and functioning.A significant strength of this study is the comparison with non-smoking controls, as withdrawal effects may be misidentified as either expected adolescent lability [9], or symptoms of more serious affective disturbance [37]. Additionally, the experimental inpatient setting reduced potential for the relative influence of tobacco related cues, increasing the strength of the observed findings as specifically related to tobacco abstinence.…”
mentioning
confidence: 99%